Effect of Different Natural Herbal Products on Microhardness of Eroded Enamel Surface: An in Vitro Study - Zeina Samir; Aisha Akram Qasim (University of Mosul, College of Dentistry, 2023)
Aims: The study aimed to evaluate and compare the effects of the herbal medicaments (Neem, Ginger, Green tea, Clove oil, and peppermint oil) and traditional fluoride gel on the surface microhardness of the eroded enamel samples of permanent teeth in vitro study. Materials and methods: A total of (80) sound maxillary first premolars were used in the study. Enamel blocks were prepared and divided into eight groups: Negative control group (C-ve) (n=10) not exposed to Pepsi drink. The remaining samples exposed to Pepsi drink then subdivided into (7) subgroups: Positive control group (C+ve) (Pepsi group), the remaining groups representing different experimental remineralizing agents used as follows: Group 3 (NaF gel), Group 4 (Neem), Group 5 (Ginger+Honey), Group 6 (Green tea), group 7 (Clove oil) and group 8 (Peppermint oil). The Microhardness of enamel blocks was measured before and after the PH cycle by using a Vickers microhardness measurement machine. Results: The microhardness of enamel surface in all study groups was decreased after eroding Pepsi drink due to the demineralization, then increased after treatment with remineralizing agents but the highest increase of the surface microhardness measurements belonged to the Ginger+Manuka group followed by Neem and NaF group, while the control negative group of deionized water which not exposed to Pepsi drink had the minimum decrease in the surface microhardness measurements. Conclusions: Ginger+Manuka honey was significantly better than other groups against demineralization and preserving enamel microhardness.